Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

2x – 3y = -7 .
2x + 3y = 11
Write your answer as an ordered pair.


Sagot :

Answer:

( 1 , 3 )

Step-by-step explanation:

Solving simultaneously, 2x - 3y = -7

-( 2x + 3y = 11)

then, 2x - 3y = -7

-2x -3y = -11

Now adding the two equations

-6y = -18 y = 3

Now substituting y in one of the equations

2x -3(3) = -7 subtracting -9 from both sides

2x = 2 x = 1